Prevalence of Infection and Changing Pattern of Organisms Causing Infections in Childhood Nephrotic Syndrome (Dhaka Shishu (Children) Hospital Journal, 2022)
Background: Infection remains an important complication of children with nephrotic syndrome. It results in significant morbidity and may also be responsible for a poor response to steroid therapy or induce relapse in child who has already attained remission.Objectives: This study was conducted to find out pattern of infection and type of organisms causing infections in nephrotic syndrome.Methods: This cross sectional study was conducted in the Paediatric Nephrology Department of Dhaka Shishu (Children) Hospital from January 2010 to November 2010. One hundred fifteen (115) cases of nephrotic syndrome, age between 1 to 13 years were enrolled according to the inclusion criteria. Along with routine investigations, urine, blood and throat swab culture and sensitivity and MT test were done. Risk factors of infection were also determined. Statistical analysis was done by SPSS version 12. Level of significance was taken as